Older workers have the competencies required by the labour market: what does it take to make realize that? - Rodrigues, Ana Raquel Cardoso de Souza; Rodrigues, Ana Cláudia; Pinto, Ana Maria (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
Population aging is widely recognized and investigated in the literature. However, despite knowledge and progress made, older workers continue to face a number of challenges in the labour market, related to age-based stereotypes and discrimination. This research intends to demystify these stigmas by analysing the self-attributed competencies held by these workers. In order to achieve this, we conducted an exploratory study, using a questionnaire addressed to the Portuguese population, active in the labour market, answered by 606 subjects. Data were analysed using statistical descriptive and frequency analyses and ANOVA’s. The results showed that older workers held the competencies most valued by the employers, mentioned in recent national and international studies. Significant differences were identified in the competencies when compared by sex, age, academic degree, years performing their function, company size, sector and younger workers. The results suggest intervention clues that can contribute to breaking stereotypes and promoting an improvement in human resources management policies, in order to increase both the recruitment and selection and training and development practices of older workers, and contribute to their maintenance in the labour market as well as their input to national organizations and economies. It contributes to the literature by challenging age discrimination and by promoting knowledge of the main competencies held by older workers. We suggest future studies that analyse these competences considering the workers' profession.